2010
DOI: 10.1002/adfm.200902114
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Grafted Gel‐Brush/Metal Nanoparticle Hybrids

Abstract: Polymer brushes are classically defined and are to date employed as assemblies of macromolecules tethered at one end to a surface. The concept of preparing surface‐grafted gels by crosslinking such brushes is attractive since it gives rise to new opportunities related to the constraints present in this type of structure. Aiming at the development of nanostructured films possessing precisely adjustable chemical, mechanical, and optical properties, the present article describes the preparation of novel grafted l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
68
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 44 publications
(52 reference statements)
2
68
0
Order By: Relevance
“…This is, to our knowledge, the fi rst time that a precise tuning of size and morphology of polymer NCs is observed by adjusting the crosslinking of a matrix template, proving the effectiveness of the approach introduced earlier for tuning the dimensional characteristics of metal NCs. [60][61][62] It is interesting to note that the increase in EGDMA crosslinker content to 30 or 50% in the matrix caused the formation of morphologically uniform polymer terraces in which no discrete assembly of P3HT could be imaged by AFM analysis (Figure 1 e and Figure S1c in the Supporting Information). To gain further information on the properties [ 22 , 57 , 58 ] These spectroscopic features confi rm the presence of P3HT crystallites in the samples.…”
mentioning
confidence: 95%
“…This is, to our knowledge, the fi rst time that a precise tuning of size and morphology of polymer NCs is observed by adjusting the crosslinking of a matrix template, proving the effectiveness of the approach introduced earlier for tuning the dimensional characteristics of metal NCs. [60][61][62] It is interesting to note that the increase in EGDMA crosslinker content to 30 or 50% in the matrix caused the formation of morphologically uniform polymer terraces in which no discrete assembly of P3HT could be imaged by AFM analysis (Figure 1 e and Figure S1c in the Supporting Information). To gain further information on the properties [ 22 , 57 , 58 ] These spectroscopic features confi rm the presence of P3HT crystallites in the samples.…”
mentioning
confidence: 95%
“…They are easily addressed, and can be used to immobilize and stabilize the NPs simultaneously with no additional stabilizers. [16][17][18][19][20][21][22] In this respect, Koenig et al [ 23 ] have shown recently that novel catalytically active surfaces can be fabricated by in situ synthesis of platinum or palladium NPs inside poly(2-vinylpyridine) (P2VP) polymer brushes. The formation process of the NPs involves two steps: fi rst, adsorption of the metal ions to the polymer brush and then reduction of the metal ions or complexes into NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted with permission from Benetti et al[35]. Copyright © 2010, Wiley VCH Verlag GmbH, KGaA, Weinheim.…”
mentioning
confidence: 96%
“…1) [35]. Benetti et al [35] established that the size of the SN and properties of the system may be altered by varying the extent of cross-linking of poly(HEMA). The grafting of poly(HEMA) onto a glass membrane surface and subsequent immobilization of SN imparts catalytic activity in the reduction of 4-nitrophenol (4NT) [36].…”
mentioning
confidence: 98%
See 1 more Smart Citation